2014
DOI: 10.1038/nrneph.2014.216
|View full text |Cite
|
Sign up to set email alerts
|

Causes and pathogenesis of focal segmental glomerulosclerosis

Abstract: Focal segmental glomerulosclerosis (FSGS) describes both a common lesion in progressive kidney disease, and a disease characterized by marked proteinuria and podocyte injury. The initial injuries vary widely. Monogenetic forms of FSGS are largely due to alterations in structural genes of the podocyte, many of which result in early onset of disease. Genetic risk alleles in apolipoprotein L1 are especially prevalent in African Americans, and are linked not only to adult-onset FSGS but also to progression of some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
223
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(234 citation statements)
references
References 122 publications
(133 reference statements)
2
223
1
8
Order By: Relevance
“…Critical is the elimination of other systemic diseases or primary renal diseases that may result in a similar presentation. Many reviews cover various aspects of FSGS and include comprehensive reviews (1)(2)(3)(4), disease mechanisms (5)(6)(7)(8), pediatric disease (9), immunologic aspects (10), treatment in children (11), and treatment in adults (12)(13)(14). We focus here on a practical approach to FSGS assessment on clinical and histopathologic grounds in the context of our current understanding of disease mechanisms and genetics.…”
Section: Introductionmentioning
confidence: 99%
“…Critical is the elimination of other systemic diseases or primary renal diseases that may result in a similar presentation. Many reviews cover various aspects of FSGS and include comprehensive reviews (1)(2)(3)(4), disease mechanisms (5)(6)(7)(8), pediatric disease (9), immunologic aspects (10), treatment in children (11), and treatment in adults (12)(13)(14). We focus here on a practical approach to FSGS assessment on clinical and histopathologic grounds in the context of our current understanding of disease mechanisms and genetics.…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown whether CSP contributes to the development of FSGS. FSGS is a heterogeneous phenotype associated with various conditions, including neoplastic conditions, HIV infections, obesity, and so on [9]. Plasma cell proliferative disorders might also be linked with FSGS.…”
Section: Discussionmentioning
confidence: 99%
“…13 Podocyte loss and dysfunction in renal microenvironments are important features in the pathogenesis of FSGS. 2 Podocyte is a unique population of terminally-differentiated glomerular visceral epithelial cell that possess distinctive morphologic features exemplified by sophisticated foot processes. 14,15 Under pathologic conditions, injurious stimuli often cause podocyte dedifferentiation characterized by loss of podocyte-specific features, thereby leading to podocyte dysfunction and defective glomerular filtration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that FSGS is the result of mutations in crucial podocyte genes. 2 Wilms' tumor-1 (WT1) is a gene that is essential for the development and maintenance of normal podocyte and glomeruli. 3,4 Loss of WT1 in pathologic conditions is commonly interpreted as a result of podocyte depletion.…”
Section: Introductionmentioning
confidence: 99%